The Correlation of Progressive Muscle Relaxation (PMR) with Massage and Aromatherapy on Reducing Menstrual Pain Intensity (Primary Dysmenorrhea) among Female Students - Badrus, Arkha Rosyaria; Khairoh, Miftahul; Purwitasari, Alief Ayu; Anggraeni, Novi; Kwarta, Cityta Putri (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2026)
Primary dysmenorrhea is one of the most common reproductive health problems experienced by adolescent girls, characterised by lower abdominal pain caused by excessive uterine contractions without any organic abnormalities. High menstrual pain intensity negatively affects learning concentration, school attendance, and overall quality of life. Non-pharmacological management approaches, such as Progressive Muscle Relaxation (PMR), massage, and aromatherapy, are considered safe and effective methods for reducing pain intensity through mechanisms including muscle relaxation, endorphin release, and parasympathetic nerve stimulation. This study aimed to evaluate the effectiveness of combining PMR, massage, and aromatherapy in reducing menstrual pain intensity among female students at Dr. Soetomo High School, Surabaya. A quasi-experimental design with a pretest-posttest control group was employed. A total of 60 respondents were selected using purposive sampling and divided into 2 groups: the intervention group (PMR + massage + aromatherapy) and the control group (health education). Menstrual pain intensity was measured using the Numerical Rating Scale (NRS) before and after the intervention. Data were analysed using a Paired t-test for within-group comparisons and normality tests to assess data distribution. The results showed a significant reduction in pain intensity in the intervention group compared with the control group (p equals 0.001). The median score in the intervention group decreased from 7.0 to 3.0, while the control group showed no significant change (p equals 0.216). The combined intervention demonstrated a large effect size (r equals 0.72), indicating a strong influence on pain reduction. Conclusion: The combination of PMR, massage, and aromatherapy is effective in reducing primary dysmenorrhea and can be recommended as a safe, affordable, and practical complementary therapy for adolescents.